Jeremiah : Being The Baird Lecture for 1922 - Smith, George Adam, 1856-1942 (Salt Lake City, UT : Project Gutenberg, 2008)
"Jeremiah: Being The Baird Lecture for 1922" by George Adam Smith is a scholarly examination of the biblical prophet Jeremiah, written in the early 20th century. This work analyzes both the life and teachings of Jeremiah, emphasizing his personal experiences, psychological depth, and poetic expressions as he navigated the complexities of his prophetic calling during a tumultuous period for Israel. The opening of this volume provides a clear framework for understanding the lectures that follow, beginning with an exploration of Jeremiah's character and the significance of his writings. Smith details Jeremiah's introspection, his struggles with faith and duty, and his profound influence on Jewish spirituality. The text reflects on how Jeremiah$1 (Bs prophecies were shaped by the historical context of his life, notably the impending Babylonian captivity, and establishes a foundation for discussing the themes that resonate through his profound and poetic expressions of sorrow, hope, and redemption. (This is an automatically generated summary.)s
Release date is 2008-11-28
Keywords: Jeremiah (Biblical prophet); Bible. Jeremiah -- Criticism, interpretation, etc